1960
DOI: 10.1083/jcb.7.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Rete Mirabile in the Kidney of the Rat as Seen with the Electron Microscope

Abstract: Electron micrographs of the fete mirabile in the medulla of the rat have rev e a l e d that the endothelium of the afferent and efferent vessels are markedly different in fine structure. The venous capillaries returning blood from the papilla a r e lined with a fenestrated endothelium much like that in the peritubular capillaries of the kidney. The arterial capillaries delivering blood to the papilla have an unperrotated lining of overlapping endothelial cells with extremely irregular tapered margins. It is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1964
1964
1975
1975

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Astrom et al (1964) and Pines (1960) reported the presence of ganglia, but they are very few in number and are found in the subcapsular region. Most workers have denied the existence of intrarenal ganglia (Mitchell, 1951 ;DeMuylder, 1952;Page & McCubbin, 1953;Longley, Banfield & Brindley, 1960;Moffat & Fourman, 1967;McGiff et al, 1967;McKenna & Angelakos, 1968a, b;Conchoa & Norris, 1968;Stinson et al, 1969). The most likely site of release of the acetylcholine is from cholinergic nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Astrom et al (1964) and Pines (1960) reported the presence of ganglia, but they are very few in number and are found in the subcapsular region. Most workers have denied the existence of intrarenal ganglia (Mitchell, 1951 ;DeMuylder, 1952;Page & McCubbin, 1953;Longley, Banfield & Brindley, 1960;Moffat & Fourman, 1967;McGiff et al, 1967;McKenna & Angelakos, 1968a, b;Conchoa & Norris, 1968;Stinson et al, 1969). The most likely site of release of the acetylcholine is from cholinergic nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
“…3B, upper arrows) and vasa recta induced by the diuretic drugs suggest that the decreased resistance in these vessels may be responsible for the relative increase in resistance in the peritubular capillaries which supply the tubules and collecting ducts in this region. Several groups (1,18,19) have now demonstrated that the vasa recta are not interspersed between the loops of Henle and collecting ducts in the outer medulla, and Thorburn et al (1) have shown that the vasa recta in this region are enclosed in a thick connective tissue sheath. Some branches to the peritubular plexus may be given off by the vasa recta, and many of the vasa recta may terminate by breaking up into coalescing branches sur- Ludwig's diagrammatic illustration of the course of the blood vessels within the cortex proper (20); m, the space occupied by the medullary radius; b, that occupied by the convoluted canals, ai, arteria interlobularis; vi, vena interlobularis; va, vas afferens glomeruli, ve, vas efferens glomeruli; gl, glomerulus; and zv, venous twig of the interlobular vein.…”
Section: Discussionmentioning
confidence: 99%
“…In both regions the particles were only found outside those vessels possessing a thin-walled fenestrated endothelium. Such vessels, in the vascular bundles of the outer medulla, can be identified as ascending vasa recta [Longley et al, 1960;Moffat, 1967;Dieterich, 1968] but in the inner medulla one cannot distinguish between ascending vasa recta and medullary capillaries, since both have endothelium of this type. The particles were usually found in the basement membrane immediately external to the endothelium ( fig.…”
Section: Resultsmentioning
confidence: 99%